The uniform act relating to general commercial law and the conflict of laws. - (:unkn) unknown (My University, 2015)
The Treaty for Business Law in Africa Harmonization was signed in Port Louis (Mauritius ) ,October 17, 1993 and entered into force on 18 September 1998. It was amended by the Treaty of Quebec on17 October 2008. This revised treaty entered into force March 21, 2010. The treaty 's main objective is toaddress the legal uncertainty and judicial existing in States parties . To do this , it adopted new Uniform Actsincluding the Uniform Act relating to general commercial law, following the AUDCG which is the subject ofour study. The OHADA Treaty has also established a Joint Court of Justice and Arbitration responsible forthe interpretation and uniform application of those acts .The AUDCG was adopted April 17, 1997 and entered into force on 1 January 1998. It was amendedDecember 15, 2010 and published in the Official Gazette of OHADA , February 15 , 2011. It entered intoforce on 15 May 2011. It is applicable in the same way in all Contracting States. The existence of such a setof rules to reduce the importance of the forum in the resolution of international disputes and reduce the needto resort to conflict rules that generate legal uncertainty. That is why OHADA law so general and especiallyAUDCG does not care or whatever conflict of laws.Yet the conflict of laws remain in OHADA . First, the AUDCG leaves the provisions of national law as longas they are not contrary to it. The AUDCG may also be subject to differing interpretations by national courtswhich are the ordinary courts of harmonized law.Furthermore, the AUDCG is part of an international legislative context involving a wealth of substantiverules subregional such as West Africa 's Economic and Monetary Union (UEMOA) , the EconomicCommunity of States of West Africa (ECOWAS ) , the Economic and Monetary Community of CentralAfrica (CEMAC) and the Economic Community of Central African States and international substantive lawsuch as the CISG , Protocol of 11 April 1980 and the New York Convention of 14 June
Keywords: African Research